Modified bibenzimidazole ligands as spectator ligands in photoactive molecular functional Ru-polypyridine units ? Implications from spectroscopy - Meyer-Ilse, Julia; Bauroth, Stefan; Braeutigam, Maximilian; Schmitt, Michael; Popp, Jürgen; Beckert, Rainer; Rockstroh, Nils; Pilz, T. David; Monczak, Katharina; Heinemann, Frank Wilhelm; Rau, Sven; Dietzek, Benjamin (Dalton Transactions, 2014)
The photophysical properties of Ruthenium-bipyridine complexes bearing a bibenzimidazole ligand were investigated. The nitrogens on the bibenzimidazole-ligand were protected, by adding either a phenylene group or a 1,2-ethandiyl group, to remove the photophysical dependence of the complex on the protonation state of the bibenzimidazole ligand. This protection results in the bibenzimidazole ligand contributing to the MLCT transition, which is experimentally evidenced by (resonance) Raman scattering in concert with DFT calculations for a detailed mode assignment in the (resonance) Raman spectra.